2018
DOI: 10.1002/widm.1294
|View full text |Cite
|
Sign up to set email alerts
|

Survey on establishing the optimal number of factors in exploratory factor analysis applied to data mining

Abstract: In many types of researches and studies including those performed by the sciences of agriculture and plant sciences, large quantities of data are frequently obtained that must be analyzed using different data mining techniques. Sometimes data mining involves the application of different methods of statistical data analysis. Exploratory Factor Analysis (EFA) is frequently used as a technique for data reduction and structure detection in data mining. In our survey, we study the EFA applied to data mining, focusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 70 publications
0
29
0
Order By: Relevance
“…On the other hand, studies on factor analysis using machine learning generally focused on factor retention (e.g. Goretzko & Bühner, 2020;Iantovics et al, 2019). Therefore, the results of the present study provide researchers with a reference point in using and selecting the most suitable machine learning method for their data structure to decide on which items will be included in which factors.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…On the other hand, studies on factor analysis using machine learning generally focused on factor retention (e.g. Goretzko & Bühner, 2020;Iantovics et al, 2019). Therefore, the results of the present study provide researchers with a reference point in using and selecting the most suitable machine learning method for their data structure to decide on which items will be included in which factors.…”
Section: Discussionmentioning
confidence: 87%
“…When studies on exploratory factor analysis using machine learning methods are examined, it can be seen that such studies generally focus on factor retention (e.g. Goretzko & Bühner, 2020;Iantovics et al, 2019). As a result of these studies, it has been reported that machine learning methods can generally be used with traditional methods.…”
Section: Randomforestmentioning
confidence: 99%
“…For the verification of the normal distribution of percentages regarding the choice of an appropriate study design [26], we used the Shapiro-Wilk test (SW test) [27]. The selection of the SW test instead of the One-sample Kolmogorov-Smirnov test or the Lilliefors test was because Shapiro-Wilk test has the highest statistical power and works well with few data [28].…”
Section: Methodsmentioning
confidence: 99%
“…Based on the in-depth bibliographic study of the scientific literature, and a previous research [16], we took into account the following three rules to determine the number of extracted factors:…”
Section: Methodsmentioning
confidence: 99%
“…Identification of an inappropriate number of factors may lead to inaccurate conclusions. A previous article studied the importance of the total cumulative variance that should be explained by the selected most appropriate number of extracted factors [16]. It was considered that, at least, a minimum threshold of cumulative variance should be explained by the extracted factors that depends on the specificity of the research.…”
Section: Introductionmentioning
confidence: 99%